Incomplete penetrance, variable expressivity, or dosage insensitivity in four families with directly transmitted unbalanced chromosome abnormalities. Issue 2 (1st December 2017) - Bateman, Mark S.; Collinson, Morag N.; Bunyan, David J.; Collins, Amanda L.; Duncan, Philippa; Firth, Rachel; Harrison, Victoria; Homfray, Tessa; Huang, Shuwen; Kirk, Beth; Lachlan, Katherine L.; Maloney, Viv K.; et al.
Abstract : The direct transmission of microscopically visible unbalanced chromosome abnormalities (UBCAs) is rare and usually has phenotypic consequences. Here we report four families in which a normal phenotype was initially found in one or more family members. Each UBCA was interpreted with regard to overlapping examples and factors previously associated with transmitted imbalances including incidental ascertainment, low gene density, benign copy number variation (CNV) content, and gene relatedness. A 4.56 Mb deletion of 8p23.1‐p23.2 was thought to be causal in the affected proband but showed incomplete penetrance in her mother and sibling (Family 1). Incomplete penetrance was also associated with a 10.88 Mb duplication of 13q21.31‐q22.1 (Family 3) and dosage insensitivity with a 17.6 Mb deletion of 22pter‐q11.21 (Family 4) that were both ascertained at prenatal diagnosis and each found in 4 unaffected family members. The 22pter‐q11.21 deletion is part of a region with high benign CNV content and supports the mapping of cat eye syndrome to a 600 kb interval of 22q11.1‐q11.21. Low gene densities of less than 2.0 genes/Mb were found in each of these three families but only after segmentally duplicated genes were excluded from the deletions of 8p and 22q. In contrast, gene density was average and variable expressivity associated with a 3.59 Mb duplication of 8p23.1 incidentally ascertained for paternal infertility (Family 2). Our results indicate that a greater degree of direct parental transmission, incomplete penetrance, and variable expression are features of both sub‐microscopic CNVs and UBCAs with relatively low gene and high benign CNV content.